Short message service prompted mouth self-examination in oral cancer patients as an alternative to frequent hospital-based surveillance - Vaishampayan, Sagar; Malik, Akshat; Pawar, Prashant; Arya, Kavi; Chaturvedi, Pankaj (South Asian Journal of Cancer, 2017)
Introduction: Oral squamous cell carcinoma (OSCC) are amongst commonest cancer in the Indian sub-continent. After treatment, these patients require frequent followup to look for recurrences/second primary. Mouth Self Examination (MSE) has a great potential in all levels of prevention of oral cancer. However, the compliance to self-examination has been reported as poor. Mobile phone is a cheap and effective way to reach out to people. Short Message Service (SMS) is extremely popular can be a very effective motivational and interactive tool in health care setting. Methodology: We aimed to identify in adequately treated OSCC patients, the influence of health provider initiated SMS on the compliance to the MSE and to establish the efficacy of MSE by comparing patients' MSE interpretation via replies to the SMS with that of the experts' opinion on clinical examination status during follow up. Conclusion: We conclude that MSE can be very useful in adequately treated OSCC patients for evaluating disease status. All treated OSCC patients must be adequately educated for MSE as an integral part of treatment & follow-up protocol by the health provider facility. Health provider generated SMS reminders do improve motivation and compliance towards MSE but don't seem to reduce dropouts in follow up for large and diverse population like that in India.
Keywords: Mouth self-examination; oral squamous cell carcinoma; short message system; surveillance